New Forest, Dehradun, India: a Unique Man-made Habitat for Butterflies in the Lower Western Himalayas - Singh, Arun P. (Indian Forester, 1999)
Butterflies were collected for six years from New Forest campus which is a man-made habitat covering an area of 4.45 km2 and located at Dehra Dun in Northern India. The aim of the study was to know butterfly species composition of this artifical habitat in relation to the Western Himalayas and also the number of larval food plant species of butterflies supported by this habitat. A total of 148 species belonging to 10 families and sub-families were found in New Forest which was one-third of the total found in the region. Three species found were ’rare’ as listed in the Schedule II of the Indian Wildlife Protection Act (1972, ammended 1989). Larval food plants for all the butterfly species were present in New Forest. The proportions all the butterfly species in the families found here were in constancy with the region and were more closely related to the Western Himalaya, as compared to the Central Himalaya or the entire Indian Sub-Continent. All these findings suggest that New Forest provides a refuge for a large number of butterfly species found in the region, depicting a point diversity.